I'll be there (but I'll be wearing sweatpants) : finding unfiltered, real-life friendships in this crazy, chaotic world - Weatherly, Amy, 1983-; Johnston, Jess, 1985- (Nelson Books, 2022)
"Amy Weatherly and Jess Johnston, founders of the wildly popular "Sister, I Am with You" online community, address common obstacles to true connection and offer a confessional, hilarious, and practical guide for building deep friendships in the middle of this crazy, rollercoaster life"--